The use of clickers to assess knowledge in foreign language classes and their failure to increase reading compliance - Juan Pablo Rodríguez Prieto (Revista de Lingüística y Lenguas Aplicadas, 2014)
This is the firstquantitative research on reading compliance in FL courses. It investigated theeffect of clickers on learning gains for regularly assigned readings, determinedby 16 quiz grades during a semester. 38 intermediate L2 Spanish studentsassigned to two group conditions also completed a questionnaire at the end ofthe semester about their preparedness for the quizzes and their opinions aboutthe use of clickers. Results indicated that participants in the Clickercondition obtained significantly lower grades in the quizzes than those in thePaper and Pencil one, despite clickers receiving positive feedback andcomments, and even though students in the Clicker condition reported preparingfor class more often than those in the Paper and Pencil condition.